The unsigned exemption clauses: a study on the legal issues from the perspective of hotel managements / Anisah Ruzaila Yaacob, Dayang Tiziana Datu S.Bahrun and Dianne Do' Ngau - Yaacob, Anisah Ruzaila; Datu S.Bahrun, Dayang Tiziana; Do' Ngau, Dianne (2009)
Most of the hotel management do not aware about the rules and common law principles on exemption clauses until there is dispute arises in their premises. This raises a question whether there is actually any guideline for them to construct the exemption clause. This research is actually an attempt to critically determine the hotels' rights in putting up exemption clauses for its guests. Besides that, this research will also examine whether there is any provision in our law that stated clear guidelines in constructing an exemption clause in term of the unsigned document. Data and information of this research were gathered from library, internet databases and interviews. Findings showed that the hotel management who put up the exemption clause is regarded as the best way to avoid the guest from taking advantage toward the hotel management. However, in cases that involve negligence, the hotel management will still be liable. It is hoped that this research can be a useful guideline to the concerned parties (especially the hotel management) to apply the appropriate rule on exemption clause.